2017
DOI: 10.1080/10495398.2017.1322973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin E and Polyunsaturated Fatty Acids on Cryopreserved Sperm Quality inBos taurusBulls Under Testicular Heat Stress

Abstract: Taurine bulls are highly susceptible to heat stress, leading to increased oxidative stress (OS) and impaired sperm viability. Polyunsaturated fatty acids (PUFAs) supplementation can be an alternative to improve semen quality, which also results in more sperm susceptibility to lipid peroxidation. Moreover, this deleterious effect can be exacerbated in animals affected by heat stress. Vitamin E is a key antioxidant that counteracts lipid peroxidation of sperm membrane caused by OS. Thus, combining PUFAs with vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
16
1
Order By: Relevance
“…The several previous studies in farm animals showed positive effects of Se and/or Vit. E on semen quality in goats (Shi et al, 2010), sheep (Liu et al, 2014) and bulls (Losano et al, 2018). Contrary to current study, no effect of Se and/or Vit.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The several previous studies in farm animals showed positive effects of Se and/or Vit. E on semen quality in goats (Shi et al, 2010), sheep (Liu et al, 2014) and bulls (Losano et al, 2018). Contrary to current study, no effect of Se and/or Vit.…”
Section: Discussioncontrasting
confidence: 90%
“…Vit. E has also been reported to reduced testicular oxidative stress (Tvrdá et al, 2016) and improve sperm quality in bulls under testicular heat stress (Losano et al, 2018). Vit.…”
Section: Introductionmentioning
confidence: 97%
“…It well known that estimation of melandialdehyde (MDA) in the seminal plasma is an end product of lipid peroxidation helps to assessing the extent of cellular damage; when cells membrane damage caused irreversible lose in essential metabolites and enzymes (Talluri et al, 2017). Also, Losano et al (2018) demonstrated that extender contains high PUFAs resulting in more susceptible spermatozoa membrane to ROS that leads to damages in membrane matrix and causes destruction of membrane structural and biochemical organs of sperm. High enzyme activity around spermatozoa in the extra medium is sign to injury sperm membrane regard cold shock as well as unsuitable concentration of extender ingredients (Sharafi et al, 2015;Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E plays a key role in protecting spermatozoa against lipid peroxidation (Agarwal, ; Zubair, ). Supplementation with vitamin E showed a beneficial effect on the semen quality in humans (Suleiman, Ali, Zaiu, El‐Malik, & Nasr, ), boars (Marin‐Guzman et al., , ), bulls (Losano et al., ) and male sheep (Yue, Yan, Luo, Xu, & Jin, ).…”
Section: Introductionmentioning
confidence: 99%